Screening tools for osteoporosis in India: Where do we place them in current clinical care? - Kripa Elizabeth Cherian; Nitin Kapoor; Meeta Meeta; Thomas Vizhalil Paul (Wolters Kluwer Medknow Publications, 2021)
The prevalence of osteoporosis is about 40%-50% in postmenopausal women and 20% in older men. The limited availability of dual-energy X-ray absorptiometry (DXA) scanners across the country calls for the presence of alternate risk assessment tools to identify those at high risk for osteoporosis. Some of the screening tools available for osteoporosis include Simple Calculated Osteoporosis Risk Estimation and Osteoporosis Risk Assessment Tool for Asians (OSTA), and Fracture Risk Assessment Tool to assess fracture risk. Clinical parameters that may serve as surrogates include dentition and anthropometric indices. Although screening tools do not supplant the assessment of bone mineral density by DXA, they help identify individuals at high risk for osteoporosis who may be selectively referred for confirming the same.